River Transport as an Instrument for the Development of Logistics System in Ukraine - Romanchuk Svitlana V. (Bìznes Inform, 2020)
The present stage of development of society is characterized by extremely high rates of reproducing processes, dynamics of business relations and high level of requirements for the efficiency of solving current problems. The article examines the composition and prospects of the logistics system in Ukraine, analyzes the strategic directions of its development. The potential of river transportation in Ukraine, its present-time status and role in the transport and logistics system are covered. Some programs for the development of the transport system and its integration into the international space, their prospects and the reality of implementation are analyzed. The main risks for sustainable development and ways of their leveling with the help of infrastructural elements are defined. The focus is set on the main problems of both the entire logistics complex and the river transportation segment, the directions of their overcoming are singled out. For the purposes of the research, with the river routes are included the immediate shipping routes (i.e. rivers and canals), infrastructure objects (ports, gateways, docks, ship repair plants, etc.) and fleet (river vessels, tugs, barges and vessels of the river-sea type). The groups of measures for the development of river transport are singled out on the basis of potential sources of their financing. The components of economic efficiency of river transport development and ways of achieving such efficiency are substantiated. The river transport of Ukraine is the most environmentally friendly, energy efficient and can provide low self-cost of transportation. In the context of perspective increase in prices for both road and rail transportation, river transport can become the reserve that can keep the cost of transportation within the country at the current level. Particular attention is paid to the development of river ports of Ukraine as promising logistics centers. Specific instruments and measures to develop the relevant segment of river logistics and ensure their efficiency have been formulated. One of these key instruments, according to the author, be the automation of the processes of management and organization of river transportation, which will help maximize their efficiency.